Post-Streptococcal Uveitis - Konovalova N.V; Savko V.V; Khramenko N.I; Guzun O.V; Slobodianyk S.B; Zhuravok Iu.A; Savko V.V (Ukrainian Society of Ophthalmologists, 2020)
Post-streptococcal uveitis refers to the most severe inflammatory conditions of the eye. It often affects young people leading to incapacity for work and physical disability. The clinical features, diagnosis, and treatment of uveitis after a streptococcal infection are described in the paper.